Pendampingan Pajak Bagi Pelaku UMKM Desa Siangan Agar Taat Administratif - Wirawan, I Made Dwi Sumba; I Made Dwi Harmana; I Wayan Chandra Adyatma (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2023)
The state has a role in providing support to MSMEs, but MSMEs often face significant challenges, especially in terms of taxation. One of the main challenges faced by MSMEs is the lack of understanding of taxation caused by a lack of understanding of taxation, a low level of awareness, and the perception that the process of paying or managing taxes is complicated. The results of community service are in the form of understanding of Siangan Village MSME actors of the importance of orderly tax administration. From the community service activities that have been carried out in Siangan Village, it will provide additional education about MSME taxation and tax administration that should be carried out by MSMEs.